Kepemimpinan Kepala Sekolah dalam Meningkatkan Sumber Daya Manusia (Studi Kasus di SD Glagaharum Kabupaten Sidoarjo) - Satunggale Kurniawan kamil (Indo-MathEdu Intellectuals Journal, 2023)
Leadership is the most important factor in supporting the achievement of school organizational goals. The success of the school principal in managing the office, managing school infrastructure, fostering teachers, or managing other school activities is largely determined by the leadership of the school principal. If the principal can mobilize, guide and direct members appropriately, all activities in the school organization will be carried out effectively. On that basis, the researchers conducted research on the implementation of school principal leadership to improve human resources at Public Alementary school Glagaharum, Sidoarjo Regency. The approach in this study was qualitative research. In this study the issues raised were activities related to the leadership of the principal to increase human resources carried out by Public Alementary school Glagaharum, and for good principal leadership can make members trust, loyal, and motivated to carry out organizational tasks effectively. optimal. For this reason, the success of the principal's leadership can be seen from the performance of the members. One factor that shows the performance of members is their work motivation. Keywords: increasing school human resources